25 Treatment escalation plans in cancer care during the COVID-19 pandemic. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Short, Oscar; Morley, Olivia; Davidson, Michael; Hadjimichalis, Alexandra; Tweddle, Andrew
Abstract : Introduction: Treatment escalation plans (TEP) enable the documentation of senior clinician-led and patient-centred advance care planning. The COVID-19 pandemic highlighted the importance of early decision-making regarding treatment escalation and early palliative care involvement. At the Royal Marsden Hospital, a TEP form was created collaboratively by Palliative Care and Acute Oncology teams in response to the pandemic. It detailed current issues including cancer diagnosis, possible clinical interventions and prognosis. Methods: A retrospective study was performed of TEP completion in non-elective admissions from 6th-27th April 2020. We reviewed patient factors including prognosis, DNACPR status, palliative care involvement and patient outcomes using electronic patient records and TEP forms. A survey was emailed to all clinical staff for feedback on the TEP forms and their impact. Results: Of the 197 non-elective admissions, 105 (53.3%) had a TEP completed. Compared to those without a TEP, patients who had a TEP completed were more likely to be on a non-curative than curative treatment pathway (91/105 (86.6%) vs 50/92 (54.3%; p<0.001 Ï‡2), have a documented DNACPR status (78.1% vs 18.5%; p<0.001 Ï‡2), have palliative care input (55.2% vs 25%; p<0.001 Ï‡2) or died (18.1% vs 6.5%; p=0.015 Ï‡2) during admission. Suspected or confirmed COVID-19 infection did not impact upon TEP completion in this cohort. The online survey was completed by 59 staff members including 30 consultants. 74.5% respondents felt that the TEP form had a positive impact on patient care, with comments on possible refinements and improvements given. Conclusions: In a specialist cancer centre rates of completion of TEP forms were higher in non-curative patients receiving increased levels of palliative care input. The TEP form had a perceived positive impact on patient care amongst clinicians, although overall uptake was disappointing. We plan to update the TEP form in response to feedback, and re-audit after 6 months.